Characterization of Family Farming in the Semi-Arid Region of Bahia - Nascimento, Deise Cristiane do; Santos, Maria Herbênia Lima Cruz (Journal of Agricultural Studies, 2021)
The article aims to characterize the transformations that have occurred in family agriculture by examining the social, economic and political aspects in the semi-arid region of Bahia. It has as its central axis the statement that the rural world remains an important category for the analysis of relations among social classes. For this purpose, a bibliographic review was carried out on the subject, as well as the legal frameworks that legitimize the insertion of family agriculture. This study opted for the adoption of the dialectical materialism method, since the semi-arid region is part of a set that materializes in social, economic and political relations, influencing and receiving influence from the environment. Moreover, based on data from the 2017 Agricultural Census, a quantitative analysis was made by comparing establishments belonging to the family and non-family agriculture categories. Finally, it is believed that this study may contribute to understanding the characteristics of family agriculture and encourage seeking actions and public policies that consider the peculiarities of the farmers' way of life.